Case Report: Large Granular Lymphocyte Leukemia (LGLL)—A Case Series of Challenging Presentations - Pflug, Natali; Littauer, Annika; Beverungen, David; Sretenovic, Aleksandra; Wahnschaffe, Linus; Braun, Till; Dechow, Annika; Jungherz, Dennis; Otte, Moritz; Monecke, Astrid; Bach, Enrica; Franke, Georg-Nikolaus; et al. (Frontiers in Oncology, 2022)
Large granular lymphocytic leukemia (LGLL) represents a rare group of diseases with considerable difficulties in their correct diagnostic work up and therapy. The major challenges lie in their distinction from reactive (including autoimmune) lymphoproliferations. Moreover, monoclonal LGL proliferative diseases are in fact a heterogeneous group of diseases, as recognized by its three subtypes in the current WHO classification, namely the two chronic forms T-LGLL and chronic lymphoproliferative disorders of NK cells (CLPD-NK) as well as aggressive NK-cell leukemia. In practice, the variable clinical presentations and phenotypes of LGLL are underappreciated. The relevant differential diagnoses range from benign reactive T-cell expansions to highly aggressive -neoplasms. T-LGLL or CLPD-NK patients suffer from a wide variety of clinical symptoms often including, but not limited to, cytopenias or classical autoimmune phenomena. They receive treatments ranging from mere supportive measures (e.g. antibiotics, growth factors, transfusions) over strategies of immunosuppression up to mild anti-leukemic therapies. The diagnostic pitfalls range from recognition of the subtle T-cell proliferation, repeated establishment of monoclonality, assignment to a descript immunophenotypic pattern, and interpretations of molecular aberrancies. Here, we report a series of selected cases to represent the spectrum of LGLL. The purpose is to raise awareness among the scientifically or practically interested readers of the wide variety of clinical, immunological, and phenotypic features of the various forms of LGLL, e.g. of T-cell type, including its gamma-delta forms or those of NK-lineage. We highlighted the characteristics and courses of five unique cases from three academic centers, including those from a prospective nationwide LGLL registry. Each case of this instructive catalogue serves to transport a key message from the areas of (chronic inflammatory) contexts in which LGLL can arise as well as from the fields of differential diagnostics and of various treatment options. Implications for optimization in these areas will be discussed.